2013
DOI: 10.1021/ml4000063
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Dabrafenib: A Selective Inhibitor of Raf Kinases with Antitumor Activity against B-Raf-Driven Tumors

Abstract: Hyperactive signaling of the MAP kinase pathway resulting from the constitutively active B-Raf(V600E) mutated enzyme has been observed in a number of human tumors, including melanomas. Herein we report the discovery and biological evaluation of GSK2118436, a selective inhibitor of Raf kinases with potent in vitro activity in oncogenic B-Raf-driven melanoma and colorectal carcinoma cells and robust in vivo antitumor and pharmacodynamic activity in mouse models of B-Raf(V600E) human melanoma. GSK2118436 was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(184 citation statements)
references
References 11 publications
5
167
0
Order By: Relevance
“…To identify potent inhibitors of dimeric BRAF, we compared eight structurally diverse RAF inhibitors: AZ-628 (AZ) (McDermott et al, 2007), TAK-632 (TAK) , LY3009120 (LY) (Peng et al, 2015), GDC-0879 (GDC) (Hoeflich et al, 2009), SB-590885 (SB) (King et al, 2006), PLX7904/Paradox Breaker (PB), which does not to induce paradoxical activation in wild-type BRAF cells , Vemurafenib (VEM) and Dabrafenib (DAB) (Rheault et al, 2013) (Figure S1A, Table S1). To compare potencies of inhibitors in cells endogenously expressing monomeric or dimeric BRAF V600E , we treated parental (PAR) SKMEL239 cells expressing full length BRAF V600E and the SKMEL239 derivative (clone C3) that is resistant to VEM due to enhanced dimerization of endogenous splice variants of BRAF V600E that lack the RAS-binding domain (Poulikakos et al, 2011).…”
Section: Structurally Diverse Raf Inhibitors Equi-potently Inhibit Momentioning
confidence: 99%
“…To identify potent inhibitors of dimeric BRAF, we compared eight structurally diverse RAF inhibitors: AZ-628 (AZ) (McDermott et al, 2007), TAK-632 (TAK) , LY3009120 (LY) (Peng et al, 2015), GDC-0879 (GDC) (Hoeflich et al, 2009), SB-590885 (SB) (King et al, 2006), PLX7904/Paradox Breaker (PB), which does not to induce paradoxical activation in wild-type BRAF cells , Vemurafenib (VEM) and Dabrafenib (DAB) (Rheault et al, 2013) (Figure S1A, Table S1). To compare potencies of inhibitors in cells endogenously expressing monomeric or dimeric BRAF V600E , we treated parental (PAR) SKMEL239 cells expressing full length BRAF V600E and the SKMEL239 derivative (clone C3) that is resistant to VEM due to enhanced dimerization of endogenous splice variants of BRAF V600E that lack the RAS-binding domain (Poulikakos et al, 2011).…”
Section: Structurally Diverse Raf Inhibitors Equi-potently Inhibit Momentioning
confidence: 99%
“…Taken together, these results provide a full understanding of dabrafenib disposition in humans. (Adams et al, 2009;Rheault et al, 2013). Chemicals and solvents of reagent or high-performance liquid chromatography (HPLC) grade were purchased from commercial sources.…”
Section: Introductionmentioning
confidence: 99%
“…These FDA-approved agents demonstrated significant clinical benefit for melanoma patients harboring BRAF V600 mutation (Flaherty et al, 2010;Chapman et al, 2011;Hauschild et al, 2012). In preclinical studies, vemurafenib and dabrafenib showed effective suppression of MEK1/2 and ERK1/2 signaling and significant growth inhibition in tumor models expressing BRAF V600E oncogene (Joseph et al, 2010;Yang et al, 2010;Rheault et al, 2013). In clinical trials, vemurafenib demonstrated complete or partial response in majority of patients with malignant BRAF V600E melanoma.…”
Section: Development Of Braf Inhibitorsmentioning
confidence: 99%